Justice and justification reflective equilibrium in theory and practice - Daniels, Norman (Cambridge Univ. Press, 1996)
We all have beliefs, even strong convictions, about what is just and fair in our social arrangements. How should these beliefs and the theories of justice that incorporate them guide our thinking about practical matters of justice? This wide-ranging collection of essays by one of the foremost medical ethicists in the United States explores the claim that justification in ethics, whether concerning matters of theory or practice, involves achieving coherence or "reflective equilibrium" (as Rawls has called it) between our moral and nonmoral beliefs. Among the practical issues the volume addresses are the design of health-care institutions, the distribution of goods between the old and the young, and fairness in hiring and firing practices. In combining ethical theory and practical ethics this volume will prove especially valuable to philosophers concerned with ethics and applied ethics, political theorists, bioethicists, and others involved in the study of public policy.
Keywords: Rawls, John <1921-> / A theory of justice; Accès aux soins de santé; Bioéthique; Ethiek; Justice (Philosophie); Justice (Principe moral); Justice distributive; Justification (Morale); Justification; Justificação; Justiça (filosofia); Políticas públicas; Rechtvaardigheid; Éthique appliquée; Éthique médicale; Éthique; Ética médica; Ethik; Applied ethics; Justice (Philosophy); Justification (Ethics); Medical ethics; Medizinische Ethik; Philosophie; Gerechtigkeit; Rechtfertigung; Aufsatzsammlung